European Respiratory Society guidelines on transbronchial lung cryobiopsy in the diagnosis of interstitial lung diseases. Issue 5 (10th November 2022) - Korevaar, Daniël A.; Colella, Sara; Fally, Markus; Camuset, Juliette; Colby, Thomas V.; Hagmeyer, Lars; Hetzel, Juergen; Maldonado, Fabien; Morais, Antonio; Ravaglia, Claudia; Spijker, René; Tomassetti, Sara; et al.
Background: In patients with interstitial lung diseases (ILD), histopathological input is often required to obtain a diagnosis. Surgical lung biopsy (SLB) is considered the reference standard, but many patients are clinically unfit to undergo this invasive procedure, and adverse events, length of hospitalisation and costs are considerable. This European Respiratory Society (ERS) guideline provides evidence-based clinical practice recommendations for the role of transbronchial lung cryobiopsy (TBLC) in obtaining tissue-based diagnosis in patients with undiagnosed ILD. Methods: The ERS Task Force consisted of clinical experts in the field of ILD and/or TBLC and methodological experts. Four PICO (Patient, Intervention, Comparator, Outcomes) questions and two narrative questions were formulated. Systematic literature searches were performed in MEDLINE and Embase (up to June 2021). GRADE (Grading, Recommendation, Assessment, Development and Evaluation) methodology was applied. Results: In patients with undiagnosed ILD and an indication to obtain histopathological data: 1) TBLC is suggested as a replacement test in patients considered eligible to undergo SLB, 2) TBLC is suggested in patients not considered eligible to undergo SLB, 3) SLB is suggested as an add-on test in patients with a non-informative TBLC, 4) no recommendation is made for or against a second TBLC in patients with a non-informative TBLC and 5) TBLC operators should undergo training, but no recommendation is made for the type of training required. Conclusions: TBLC provides important diagnostic information in patients with undiagnosed ILD. Diagnostic yield is lower compared to SLB, at reduced serious adverse events and length of hospitalisation. Certainty of the evidence is mostly "very low". Transbronchial lung cryobiopsy provides important diagnostic information in patients with undiagnosed interstitial lung diseases https://bit.ly/3MAR4wc